2005
DOI: 10.1634/stemcells.2004-0331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Optimal Culture Conditions for Clinical Scale Production of Human Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells defined by multilineage potential, ease to gene modification, and immunosuppressive ability, thus holding promise for tissue engineering, gene therapy, and immunotherapy. They exhibit a unique in vitro expansion capacity, which, however, does not compensate for the very low percentage in their niches given the vast numbers of cells required for the relative studies. Taking into consideration the lack of a uniform approach for MSC isolation and expansion, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
424
5
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(464 citation statements)
references
References 52 publications
23
424
5
12
Order By: Relevance
“…11 In our study, an aberrant HLA-DR expression on BM-derived MSCs was documented in some LPD, thus suggesting unreported possible interactions between BM stromal cells and early lymphoid progenitor cells. Furthermore, because cytokines treatment (IL-1b, INF-y and TGF-b) was reported to modulate the expression of antigenpresenting molecules on cultured human fibroblasts and epithelial cells, 12 in this study, we gave evidence that HLA-DR expression on MSCs was also found to be related to different culture conditions, 13 as it was more expressed under angiogenic conditions. As MSCs heterogeneity could suggest specialization of function, the occurrence of immunophenotypic changes of ex vivo expanded MSCs could be relevant for MSCs properties; based on these considerations, we speculated that the BM microenvironmental conditions play a pivotal role in controlling MSCs function.…”
mentioning
confidence: 55%
“…11 In our study, an aberrant HLA-DR expression on BM-derived MSCs was documented in some LPD, thus suggesting unreported possible interactions between BM stromal cells and early lymphoid progenitor cells. Furthermore, because cytokines treatment (IL-1b, INF-y and TGF-b) was reported to modulate the expression of antigenpresenting molecules on cultured human fibroblasts and epithelial cells, 12 in this study, we gave evidence that HLA-DR expression on MSCs was also found to be related to different culture conditions, 13 as it was more expressed under angiogenic conditions. As MSCs heterogeneity could suggest specialization of function, the occurrence of immunophenotypic changes of ex vivo expanded MSCs could be relevant for MSCs properties; based on these considerations, we speculated that the BM microenvironmental conditions play a pivotal role in controlling MSCs function.…”
mentioning
confidence: 55%
“…The DJ9 corresponding antigen, HLA-DR is normally expressed in antigen presenting cells, and not MSCs . However, expression of HLA-DR in cultured MSCs has been described previously as a result of induction by interferon-Îł (Chan et al, 2008) or basic fibroblast growth factor (Sotiropoulou et al, 2006) present in the culture medium. Thus, the expression of HLA-DR in telemorase immortalized MSCs, but not primary derived MSCs, may reflect the long term in vitro culture of these cells.…”
Section: Discussionmentioning
confidence: 94%
“…Refl ecting the complexity of the stromal system in bone marrow, MSC populations expanded from marrow aspirates are heterogeneous in nature with the exact composition depending on the donor (Rickard et al, 1996;Majors et al, 1997;Muschler et al, 2001), the individual aspirate (Lazarus et al, 1997;Muschler et al, 1997;Phinney et al, 1999;Muschler et al, 2001;Hernigou et al, 2006), applied isolation methods and expansion conditions, the latter of which differ largely among investigators (Phinney, 2002;Shahdadfar et al, 2005;Sotiropoulou et al, 2006;Mannello and Tonti, 2007;Wagner and Ho, 2007). Cloned populations of MSC demonstrate that only part of the cells is multipotent while the remaining population shows varied phenotypes (Russell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%